SMEs, Wealth Creation and Poverty Alleviation in Nigeria - Asikhia, Olalekan Usiobaifo (Journal of Economics and Behavioral Studies, 2016)
Most developing countries see small and medium-scale enterprises (SMEs) as engines of development, and as such formulate policies that could encourage their establishment and survival. However, in spite of the enormous number of such firms established and operating, the Nigerian economy is still far from being buoyant. This article reports on research testing the wealth creation model applicable to SMEs and investigated the contribution of SMEs to poverty alleviation in Nigeria. A survey of 581 SMEs was conducted and the findings revealed that only 15% of wealth created that contributed to alleviating poverty was traceable to SMEs. This increased to 24% when moderated with wealth distribution, but by only one percent when moderated by wealth motivation. This implies that although most SME operators in Nigeria have personal motivations to acquire wealth, they are not distributing it, hence the low percentage of wealth that SMEs contribute to poverty alleviation. Policy implications and recommendations were made.